Effect of Coating and Coated Paperboard Packaging on the Quality of Grapes and Apple during Storage - Soriful Islam; Md Shakil; Md Sazzat Hossain Sarker; Md Faridunnabi Nayem; Tanjina Akter; Ishmam Haque Sachcha; Sabina Yasmin (Journal of Food Quality)
Edible coatings and active packaging have become more prevalent in response to changing consumption patterns and market trends to enhance the quality and safety of fresh products. In this work, we investigated the effect of aloe vera gel (AVG) coating and paraffin wax-coated paperboard (PWB) packaging on the postharvest quality attributes of both grapes and apples during storage. The fruits were coated with 50% AVG concentrations, and the inner wall of the corrugated paperboard was coated with paraffin wax emulsion. The grapes and apples were stored for 12 and 35 days, respectively, at ambient conditions (25 ± 3°C and 80–85% relative humidity). The physicochemical properties, microbiological attributes, and decay incidence of the fruits were analyzed at intervals during storage. Both fruits treated with AVG and PWB packaging retained better qualities than the control at the final day of the storage period. Particularly, PWB packaging provided considerably superior quality from the control sample in terms of weight loss (≈54% and 32%), firmness (≈48% and 68%), and color difference (≈30% and 28%) for both grapes and apples. These findings would introduce a novel approach for preserving the quality attributes of both climacteric and nonclimacteric fruits for a prolonged storage period at ambient temperature by PWB packaging and AVG coating.